Human Rights in Albania: Protection under the European Convention on Human Rights - Alimehmeti, Evis (European Integration Studies, 2025)
The paper sheds light on some of the current challenges of human rights protection in Albania, through a historical overview of the constitutional framework of such protection, the place of international law in the national system, in particular the European Convention on Human Rights and the findings of the European Court of Human Rights. It shows that, whereas the constitutional and legal framework aligns with the standards of protection of human rights enshrined in the Convention, the findings of the Court in the last two decades indicate continuous challenges yet to be addressed in relation to several rights and freedoms, especially those concerning the guarantees related to fair trial, lengthy court proceedings, property rights, and effective remedies.